Balai Bomba dan Penyelamat Pagoh Muar Johor / Amirul Hafiz Nasir - Nasir, Amirul Hafiz (Universiti Teknologi Mara, Perak, 2016)
This report, described about the types and materials that use on beam on site of “Cadangan membina dan menyiapkan bangunan Balai Bomba Dan Penyelamat dan lain-lain kerja yang berkaitan di Pagoh, Muar, Johor. This report was reported based on the observation and experience of four months at the construction project. This report is divided into several parts with beginning with an introduction, organizational background, case study, problem and recommendation, and conclusion. From the observation, the installation and operation process of ground beam were very complex. This report explain how to install the ground beam and reinforcement bar at site project very detail step by step. Then, this report delivered some suggestions to solve the problem. In conclusion, this report explained and described about the types and materials of beam at site project that involve in this report.